ANALISIS FAKTOR YANG MEMENGARUHI PELAKSANAAN INISIASI MENYUSUI DINI (IMD) DIUPT PUSKESMAS GAJAH MADA DAN TEMBILAHAN HULU - Mia Rita Sari (Jurnal Kesehatan Husada Gemilang, 2019)
Early Breastfeeding Initiation (EIB)is placing the baby on his stomach on the mother's chest or abdomen so that the baby's skin is attached to the mother's skin, which is done at least one hour immediately after birth. The percentage of newborns who received EIB in 2016 was 51.9% which consisted of 42.7% getting an EIB in less than an hour after birth, and 9.2% in an hour or more. WHO data (2010) showed neonatal deaths occurred on the first day. Giving EIB and continuing with exclusive breastfeeding for 6 months can prevent infant death. Based on the initial survey in 2 Community Health Center (CHC), it was found that the implementation of EIB was only carried out for normal maternity mothers (92% and 29%). This study drives the analysis of factors that encourage the implementation of the early initiation of breastfeeding at CHC of Gajah Mada and Tembilahan Hulu in 2018. The techniques of collecting data was primarily open-ended questionnaire with interview. In analysing the data, the researcher used univariate and bivariate analysing technique to show that there were correlation among knowledge (p value = 0.011), attitude (p value = 0.030), training (p value = 0.030) and the implementation of EIB at CHC of Gajah Mada and Tembilahan Hulu in 2018. It highly expected that midwives are to maintain good performance in EIB implementation by participating in trainings that are related to EIB in the APN series, participating in the regulation socialization of EIB, and providing information about EIB to pregnant women and their families during ANC visits.